1970
DOI: 10.1063/1.1653406
|View full text |Cite
|
Sign up to set email alerts
|

SPONTANEOUS AND LASER EMISSION FROM Pb1−xSnxTe DIODES PREPARED BY Sb DIFFUSION

Abstract: Impurity diffusion, using the donor impurity Sb, has been used to prepare high-quality Pb1−xSnxTe (x=0.13–0.20) light-emitting diodes. The emission of 8–14 μ spontaneous and laserlike radiation from these diodes is discussed in terms of the optical gain expected at these wavelengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1971
1971
1980
1980

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…For the case of retrograde solidus lines, where the solubility of excess metal or Te decreases with decreasing temperature, as the crystal cools part of the excess can precipitate as an electrically inactive second phase. 113 In experiments on alloyed contacts to p-type and η-type PbTe, it was found that Ag, Au, and Tl behave as acceptor impurities, whereas In and Bi behave as donor impurities. Figure 16 shows that the p-type to η-type cross over temperature decreases as the Sn content increases.…”
Section: Imperfectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the case of retrograde solidus lines, where the solubility of excess metal or Te decreases with decreasing temperature, as the crystal cools part of the excess can precipitate as an electrically inactive second phase. 113 In experiments on alloyed contacts to p-type and η-type PbTe, it was found that Ag, Au, and Tl behave as acceptor impurities, whereas In and Bi behave as donor impurities. Figure 16 shows that the p-type to η-type cross over temperature decreases as the Sn content increases.…”
Section: Imperfectionsmentioning
confidence: 99%
“…Most of the early work on photo voltaic detectors has been done using the interdiffusion technique. 113 The active areas of the photodiodes have been defined by forming etched mesa structures, by cleaving, or by using photolithographically formed Si0 2 diffusion masks in the case of Pbi-^Sn^Te diodes. 107 · 170 Similarly, in Hgi_ x Cd x Te n-p junctions can be readily formed by diffusion, 171-17 3 generally by using a Hg source to form a metal-rich η-layer.…”
Section: Photovoltaic Detector Technologymentioning
confidence: 99%
“…The effect of calcium level in these alloys has been well studied (1,2,7). The literature also contains many articles on calcium-lead, covering such subjects as aging behavior (1-4, 6, 7), casting properties (2, 3, 6, 7), battery grid growth (3,5), and corrosion resistance (3,5).…”
Section: Introductionmentioning
confidence: 99%
“…A common method for obtaining n-p junctions in Pbl~xSn.~Te is to diffuse a metal-rich layer into the p-type substrate (1). An alternative method which has proven quite successful involves diffusing a donor impurity such as Sb into the p-type substrate (2,3)~ This paper will discuss some of the characteristics of Sb diffusion into p-type Pbl-xSn~Te determined from radioactive Sb profiles and junction depths found by thermoelectric probe measurements. The ranges of temperatures, alloy compositions, and substrate hole concentrations which were studied are those of importance in the fabrication of junction lasers and photovoltaic detectors for the 8-12 ~n spectral region.…”
mentioning
confidence: 99%
“…I n order to provide p-n junctions the material is usually annealed a t relatively low temperatures for long times. This process removes metal vacancies [4] and changes the majority carrier type from p to n. Recently, however, impurity diffusion has been reported [5]. I n order to reduce the time required for annealing, we have taken the approach of growing an epitaxial layer at a low tempera-A.…”
Section: Introductionmentioning
confidence: 99%